Docking studies of Physalis peruviana ethanol extract using molegro virtual docker on insulin tyrosine kinase receptor as antidiabetic agent (International Current Pharmaceutical Journal, 2014)
Physalis peruviana Linn in Indonesia was better known as ciplukan, based on information from urban people in Indonesia is as antidiabetic. In the previeous studies, the levels of blood glucose in animals experimental of Physalis peruviana quantified with glucometer and compared with oral antidiabetic drugs gliclazide, showed that Gliclazide was decrease more levels of glucose significantly than ethanol extract of Physalis peruviana. We have done molecular docking using Molegro Virtual Docker (MVD) on ethanol extract of Physalis peruviana and gliclazide to compare between in silico and in vivo studies. Based on studies before the main content of the ethanol extract of Physalis peruviana were withanolide, 4-OH-withanolide, and perulactone. In this study the results showed that gliclazide had been better bond in insulin tyrosine kinase receptor than main content of Physalis peruviana which can be seen from Moldock score 105.217 and Rerank score -68,2931 means that the energy was lower and more stable binding. Moldock Score of main content Physalis peruviana (withanolide, 4-OH-withanolide, and perulactone) were -93.5472; 70.5843; 88.7881, respectively. Rerank score of main content Physalis peruviana (withanolide, 4-OH-withanolide, and perulactone) were -61.5149; -67.5345; -65.7979, respectively. The hydrogen bonds of withanolide, 4-OH-withanolide, perulactone and gliclazide with amino acid of insulin tyrosine kinase receptor were Phe 1186 and Thr 1186. Finally, in the 3D MVD visualization between main content of ethanol extract of Physalis peruviana and gliclazide can be concluded that interaction of gliclazide was more harmonious than main content of ethanol extract Physalis peruviana.DOI: http://dx.doi.org/10.3329/icpj.v3i5.18534 International Current Pharmaceutical Journal, April 2014, 3(5): 265-269